Transtornos psiquiátricos em pacientes com hepatite C crônica: implicações clínicas e biomarcadores - Bruno Copio Fabregas (2015)
Psychiatric disorders are more prevalent in chronic hepatitis C (CHC) patients when compared with general population. The association between interferon alpha (IFN-) use and major depressive disorder (MDD) has been reported in the literature. The objective of this work was to evaluate psychiatric symptoms and disorders, health related quality of life (HRQL) and biomarkers in CHC patients using or not IFN-. Therefore one hundred and five outpatients attended in a public reference service of infectious diseases in Belo Horizonte were evaluated in the period from May 2009 to April 2013. The evaluation included psychiatric structured interview, M.I.N.I.-PLUS, psychopathological and HRQL questionnaires and scales (Hamilton Depression Scale; Hamilton Anxiety Scale; Beck Depression Inventory; Hospital Anxiety and Depression Scale; Brief Fatigue Inventory; Barratt Impulsiveness Scale; World Health Organization Quality of Life Scale - Brief Version) and plasma analysis of BDNF, TNF-, sTNFR1, sTNFR2, adiponectin, leptin and resistin. Sociodemographic, epidemiological and clinical data were also collected and analyzed. An elevated prevalence of psychiatric disorders was found, affecting 59% of all patients. Major depression was the most common diagnosis, found in 33 patients (31.4%). There was association between IFN- current use and MDD (p=0.024). Among twenty seven patients that were in current use of IFN-, fourteen (51.9%) of them presented MDD. MDD patients reported worse fatigue (p<0.001) and worse HRQL (p<0.001). MDD and fatigue were associated with worse HRQL, and married status with better HRQL. High impulsiveness was found in CHC patients, and was associated with lower educational level, current use of IFN-, alcohol use disorder, other psychiatric comorbidities, and increased suicide risk during IFN- treatment. Sexual dysfunction and dissatisfaction were found in 57.1% and 32.4% of patients, respectively. Sexual dysfunction was associated with older age, female gender, viral genotype 2 or 3, IFN- current use, impulsiveness, depressive symptoms, antidepressant use, benzodiazepine use, and worse HRQL. In the longitudinal arm of the study, lower adiponectin plasma levels were associated with higher frequency of MDD in the following interview. In conclusion, psychiatric symptoms and disorders were frequent in CHC studied patients. MDD was the most frequent psychiatric diagnosis and it was associated with IFN- use. MDD and fatigue were implicated as main contributors to HRQL worsening. High levels of impulsiveness and sexual dysfunction were found in CHC patients and they were also associated with IFN- treatment and with significant morbidity. The role of adiponectin as a resilience biomarker for MDD should be replicated in further studies.